Business as war : - Allard, C. Kenneth (John Wiley & Sons, Inc., 2004)
The book draws sometimes startling yet keenly insightful parallels between the strategies and tactics of the United States military and the challenges that companies face in the no-holds-barred world of business. Through firsthand accounts from his military and business career as well as real-world examples that apply cutting-edge military perspectives to the everyday world of business, Allard clearly illustrates how military lessons - when implemented correctly - can lead a business down the road to success.